2017
DOI: 10.1213/ane.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enhanced Recovery After Surgery and Opioid-Free Anesthesia on Opioid Prescriptions at Discharge From the Hospital: A Historical-Prospective Study

Abstract: This study is the first to report discharge opioid prescribing practices in an ERAS setting. Although an ERAS intervention for colorectal surgery led to an increase in opioid-free anesthesia and multimodal analgesia, we did not observe an impact on discharge opioid prescribing practices. The majority of patients were discharged with an opioid prescription, including those with a combination of low discharge pain scores, no preoperative opioid use, and low morphine milligram equivalents consumption before disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(129 citation statements)
references
References 27 publications
4
113
2
4
Order By: Relevance
“…Finally, the ERAS cohort had a significantly lower percentage (21.7%) of patients discharged on narcotics versus the control group (90.3%). Brandal et al looked at opioid prescribing practices following ERAS protocols in colorectal surgery . They found that patients utilized less narcotics in the hospital setting but there was no impact on opioid prescribing practices.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the ERAS cohort had a significantly lower percentage (21.7%) of patients discharged on narcotics versus the control group (90.3%). Brandal et al looked at opioid prescribing practices following ERAS protocols in colorectal surgery . They found that patients utilized less narcotics in the hospital setting but there was no impact on opioid prescribing practices.…”
Section: Discussionmentioning
confidence: 99%
“…A colorectal ERP intervention which included epidural analgesia resulted in an increase in the use of opioid-free anesthesia and multimodal analgesia but did not decrease discharge opioid prescriptions 27. It is well recognized that opioid over-prescription occurs regularly after surgery among almost all surgical specialties and opioids are not regularly prescribed in a patient-specific manner to postoperative patients28–30 and up to 71% of these opioid pills go unused 30.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pediatric data show that 4.8% of opioid-naïve individuals undergoing surgery are at risk of long-term opioid use postoperatively, with colectomy patients being at the highest risk 32. Data also show that despite ERPs leading to lower inpatient opioid consumption, the majority of colorectal surgery patients will be discharged with an opioid prescription 33. By using an ERP, we were able to discharge these patients without an opioid prescription with only one patient (1/50, 2.0%) in the unmatched ERP cohort returning for pain control issues.…”
Section: Discussionmentioning
confidence: 99%